2019
DOI: 10.1186/s40816-019-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antimicrobial, and GC-MS profiling of Saussurea obvallata (Brahma Kamal) from Uttarakhand Himalaya

Abstract: Background: Saussurea obvallata (DC.) Edgew. (S. obvallata) is an endangered medicinal herb of the high altitude Himalayan region with immense cultural significance. This study is one of the first report of pharmacological evaluation and GC-MS analysis of methanolic extracts of leaves and flowers of S. obvallata.Methods: Total flavonoid content (TFC) and total phenolic content (TPC) were performed according to standard protocols. The antioxidant activities of both the extracts (methanol and aqueous) were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Most of these compounds were proven, by many publications, to have biological activities, e.g., antimicrobial, anti-inflammatory and antioxidant [ 64 , 65 , 66 ]. Moreover, many of the major compounds and chemical groups, detected in P. ostreatus aqueous extract by GC-MS, have been reported to have antioxidant and anti-inflammatory properties; these include (S)-(+)-isoleucinol [ 67 ], N-hydroxy-N-methyl-methanamine [ 66 ], phenylethanal [ 68 , 69 ] and 2-pyrrolidinone [ 70 , 71 ]. On the other hand, GC-MS of A. bisporus extract revealed the presence of multiple antioxidant and anti-inflammatory abundant constituents and chemical groups including N-methoxy-methanamine, [ 66 ], 2-pyrrolidinone [ 70 , 71 ] and fumaric acid, 2-heptyl octyl ester [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these compounds were proven, by many publications, to have biological activities, e.g., antimicrobial, anti-inflammatory and antioxidant [ 64 , 65 , 66 ]. Moreover, many of the major compounds and chemical groups, detected in P. ostreatus aqueous extract by GC-MS, have been reported to have antioxidant and anti-inflammatory properties; these include (S)-(+)-isoleucinol [ 67 ], N-hydroxy-N-methyl-methanamine [ 66 ], phenylethanal [ 68 , 69 ] and 2-pyrrolidinone [ 70 , 71 ]. On the other hand, GC-MS of A. bisporus extract revealed the presence of multiple antioxidant and anti-inflammatory abundant constituents and chemical groups including N-methoxy-methanamine, [ 66 ], 2-pyrrolidinone [ 70 , 71 ] and fumaric acid, 2-heptyl octyl ester [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…GC-MS analysis of LE and FE mixture, component identification, and function prediction were performed according to Semwal and Painuli (2019). There were 65 peaks identified based on a separation of individual peaks, retention time, and percent area under the individual peak (Supplementary Table 2).…”
Section: Gc-ms Analyses Of Methanolic Extractmentioning
confidence: 99%
“…Few components reported in this study have already been reported as responsible for many biological activities in other plants. Additionally, various other usage of these components are known in fragrance and perfume industry, flavor, and pesticides (Raman et al, 2012;Swamy and Sinniah, 2015;Semwal and Painuli, 2019).…”
Section: Gc-ms Analyses Of Methanolic Extractmentioning
confidence: 99%
“…The taxonomic hierarchy of S. obvallata are presented in Table 1. (Amano & Ohba 2000, Ghosh 2017, Semwal et al 2019, von Raab-Straube 2013. Flowering and fruiting: July-September and August-October (Fujikawa 2010, Semwal et al 2019, von Raab-Straube 2017.…”
Section: Taxonomy and Nomenclaturementioning
confidence: 99%